2019
DOI: 10.1016/j.scienta.2018.11.049
|View full text |Cite
|
Sign up to set email alerts
|

Natural fruitlet abscission as related to apple tree carbon balance estimated with the MaluSim model

Abstract: Apple trees produce many more flower clusters than needed for a full crop, but natural early season flower and fruitlet abscission drastically reduce the final fruit number. Natural fruit abscission varies significantly year to year. There have been attempts to try to model apple fruit abscission in the past. However, due to the great complexity of a perennial crop system in a dynamic environment with significant plant manipulations, regulatory processes and controlling environmental variables have been diffic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 45 publications
9
34
0
Order By: Relevance
“…This concurs with the observations of the present study (the year 2015 was warmer than 2016). The carbohydrate balance can also play a significant role in apple tree response to fruit abscission; if the carbohydrate supply is abundant it may limit fruit development and abscission (Lordan et al, 2019). Other factors may also explain year-to-year Brevis ® efficacy, including the weather of the previous year, carbohydrate ratios from the previous year, temperature and sunlight from bud break to bloom or post bloom, tree vigor, leaf area, or the sensitivity of the tree itself.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This concurs with the observations of the present study (the year 2015 was warmer than 2016). The carbohydrate balance can also play a significant role in apple tree response to fruit abscission; if the carbohydrate supply is abundant it may limit fruit development and abscission (Lordan et al, 2019). Other factors may also explain year-to-year Brevis ® efficacy, including the weather of the previous year, carbohydrate ratios from the previous year, temperature and sunlight from bud break to bloom or post bloom, tree vigor, leaf area, or the sensitivity of the tree itself.…”
mentioning
confidence: 99%
“…Other factors may also explain year-to-year Brevis ® efficacy, including the weather of the previous year, carbohydrate ratios from the previous year, temperature and sunlight from bud break to bloom or post bloom, tree vigor, leaf area, or the sensitivity of the tree itself. Lordan et al (2019) reported how these factors can affect natural fruit abscission. The significant interactions between year and cultivars in most of the parameters evaluated can be attributed to the different efficacy between years and cultivars.…”
mentioning
confidence: 99%
“…Growers will use the flower cluster estimations to steer pruning and flower thinning, and to get early yield estimations. For example, for yield estimations, knowing the flower clusters per tree instead of per meter will probably lead to higher estimation accuracies since the flower clusters determine the amount of sinks and the carbohydrate balance of its tree, and hence determine the physiological fruit fall of one particular tree [43]. If pear trees show a gradual change in flower clusters according to their position to the neighboring trees individual tree delineation is not necessary.…”
Section: Tree Delineationmentioning
confidence: 99%
“…For the past 50 years chemical thinning sprays have been the primary method growers use to reduce fruit numbers, but despite over 50 years of experience with chemical thinning, it remains an unpredictable part of apple production with large variations from year to year and within years due to weather variables such as temperature and radiation (Robinson et al, 2017;Robinson and Lakso, 2004;Robinson et al, 2012). There have been many studies that have attempted to understand better the roles of individual factors, with experimental manipulation of cultivar, tree vigor, bloom density, environmental conditions or chemical used (Lakso and Goffinet, 2017;Lordan et al, 2019). Yet, more than 30 years of field trials (Dennis, 2000;Greene, 2002;Greene and Costa, 2012;Greene and Lakso, 2013;Robinson and Lakso, 2011;Williams, 1979) have provided only general guidelines on the effects of weather conditions and timing of application, but have not been able to clarify regulatory processes or provide quantitative rules for prediction of apple chemical thinning response.…”
Section: Introductionmentioning
confidence: 99%
“…Conditions that lead to low carbohydrate balance are associated with heavy natural fruit drop (Lordan et al, 2019) and easier chemical thinning (Robinson and Lakso, 2011). These include hot temperatures, cloudy, heavy initial set on many weak spurs and stressed trees.…”
Section: Introductionmentioning
confidence: 99%